PENGEMBANGAN MODEL PEMBELAJARAN MATEMATIKA BAGI SISWA BERKESULITAN BELAJAR DI SEKOLAH DASAR INKLUSI - Indina Tarjiah (JIV-Jurnal Ilmiah Visi, 2015)
The objective of this research is to produce a mathematic instruction model for the children with learning disabilities in multiplication. This research was conducted at the elementary school implementing inclusive education. This research performed as from June 2013 through November 2014 was categorized as a research and development with the stages starting from preliminary study by analyzing potentials and problems, collecting and analyzing all information related to the problems, designing the model, validating the model, revising the model, testing the model, revising the model, trying out the model, improving the model, and finally producing the model. The research produced instructional model consisting of several components appropriate for the students with disabilities in learning multiplication.